2006
DOI: 10.1097/01.blo.0000223998.02765.0d
|View full text |Cite
|
Sign up to set email alerts
|

Two Potential Causes of EPL Rupture after Distal Radius Volar Plate Fixation

Abstract: Rupture of the extensor pollicis longus tendon can occur after volar plate fixation of dorsally comminuted distal radius fractures. We attempted to identify the etiology of extensor pollicis longus tendon injury after volar plate fixation of the distal radius and potential solutions to this problem. After describing two case reports, we examine six cadaveric specimens and retrospectively review 10 selected patients to evaluate possible technique refinements to minimize damage to the extensor pollicis longus te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
106
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 14 publications
0
106
1
8
Order By: Relevance
“…Al-Rashid et al [31] reported an incidence of extensor tendon rupture of 8.6 % of 35 cases (three cases) treated with an AO volar locking plate, citing screw penetration of the dorsal cortex and careless drilling technique as principle causes. Other authors reporting extensor tendon irritation and ruptures have cited similar reasons [32][33][34][35]. It is worth noting that extensor tendon injury has also been reported in 5 % of undisplaced distal radius fractures, most likely due to extensor irritation over dorsal callus formation [36].…”
Section: Discussionmentioning
confidence: 91%
“…Al-Rashid et al [31] reported an incidence of extensor tendon rupture of 8.6 % of 35 cases (three cases) treated with an AO volar locking plate, citing screw penetration of the dorsal cortex and careless drilling technique as principle causes. Other authors reporting extensor tendon irritation and ruptures have cited similar reasons [32][33][34][35]. It is worth noting that extensor tendon injury has also been reported in 5 % of undisplaced distal radius fractures, most likely due to extensor irritation over dorsal callus formation [36].…”
Section: Discussionmentioning
confidence: 91%
“…Although volar plates are usually well tolerated, they can lead to impingement on the extensor tendons when the fixation screws are too long and extend beyond the dorsal cortex of the radius. This form of impingement has been reported in several articles in the orthopedics literature [8][9][10][11][12], but we are unaware of similar studies in the radiology literature.…”
Section: Sonography Of Screw Impingement On Extensor Tendons After Vomentioning
confidence: 89%
“…All were treated with Kirschner-wire fixation and not with volar plating [8]. Although the authors of several articles in the orthopedics literature have described extensor tendon tears caused by protruding screws [9][10][11][12], in none was sonography used preoperatively.…”
Section: Sonography Of Screw Impingement On Extensor Tendons After Vomentioning
confidence: 99%
“…This complication is thought to be avoidable. When volar locking plates are used, properly locating the plates and an adequate screw length are important to avoid tendon problems [2,5,13]. In the computer system, we can simulate the best location for the plates and calculate the best screw length.…”
Section: Discussionmentioning
confidence: 99%